2017
DOI: 10.3390/s17040934
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Validity of a Wearable Sensor System for Measuring Sub-Task Performance during the Timed Up-and-Go Test

Abstract: Background: The timed-up-and-go test (TUG) is one of the most commonly used tests of physical function in clinical practice and for research outcomes. Inertial sensors have been used to parse the TUG test into its composite phases (rising, walking, turning, etc.), but have not validated this approach against an optoelectronic gold-standard, and to our knowledge no studies have published the minimal detectable change of these measurements. Methods: Eleven adults performed the TUG three times each under normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 31 publications
2
52
1
Order By: Relevance
“…However, the body-worn sensors and motion capture agreed better than the App and video with respect to average gait speed (-0.017 m/s vs. -0.103 m/s, respectively). Unfortunately, Beyea et al [15] did not report 95% LOA, so we are unable to compare the random error observed here with theirs.…”
Section: -Ft Up-and-gocontrasting
confidence: 81%
See 4 more Smart Citations
“…However, the body-worn sensors and motion capture agreed better than the App and video with respect to average gait speed (-0.017 m/s vs. -0.103 m/s, respectively). Unfortunately, Beyea et al [15] did not report 95% LOA, so we are unable to compare the random error observed here with theirs.…”
Section: -Ft Up-and-gocontrasting
confidence: 81%
“…Like the present study, Beyea et al [15] additionally investigated the sit-to-stand time, gait speed, turn duration, and stand-tosit time. While the differences were statistically significant, the App here exhibited less mean difference from video analysis, compared with the difference between body-worn sensors and motion capture investigated by Beyea et al [15] for the sit-to-stand time (-0.09 s vs. -0.14 s, respectively), turn duration (-0.10 s vs. -0.23 s, respectively), and the stand-to-sit time (-0.14 s vs -0.21 s, respectively). However, the body-worn sensors and motion capture agreed better than the App and video with respect to average gait speed (-0.017 m/s vs. -0.103 m/s, respectively).…”
Section: -Ft Up-and-gomentioning
confidence: 85%
See 3 more Smart Citations